Cultural Preservation and Inclusion for the Ifugao People - Ellisiah Uy Jocson (Journal of Southeast Asian Human Rights, 2018)
This study seeks to offer insight into the paradox between two ideologies that are currently being promoted in society and identify the relationship of both towards the indigenous community of the Ifugao in the Philippines. Inclusion is a growing trend in many areas such as education, business and development. However, there is ambiguity in terms of educating and promoting inclusion for indigenous groups, particularly in the Philippines. Mandates to promote cultural preservation also present limits to the ability of the indigenous people to partake in the cultures of mainstream society. The people of the Ifugao, together with other indigenous tribes in the Philippines, are at a state of disadvantage particularly due to the discrepancies between the rights that they receive relative to the more urbanized areas of the country. The divided vantages from the desire to preserve their culture and to become inclusive in delivering equal rights and services seems to present a rift and a dilemma on which ideology to promulgate. Apart from the imbalances, the stand of the Ifugao regarding this matter is unclear, particularly if they observe and follow a central principle. Given the notions of inclusion to accommodate everyone regardless of “race, gender, disability, ethnicity, social class, and religion, it is highly imperative to provide clarity to this issue, and identify what actions to take regarding them. The study aims to understand how they are perceived, implemented and integrated and shall look for manifestations in three areas of the Ifugao, namely the Lamut, Lagawe, and Banaue. The study uses a qualitative-case study design, obtaining data through a review of documents and policies, interviews and observations in order to identify the current status of both ideologies in terms of implementation, integration and acceptance for the Ifugao people in the Philippines.